The direct effect of exercise on the mental health of scientific and technological professionals and the mediating effects of stress, resilience, and social support - Wu, Kai; Wang, Shengnan; Ding, Tengyun; Li, Yongxin (Frontiers in Public Health, 2023)
Background High working pressure is one of the main causes of occupational sub-health problems in scientific and technological professionals. With the development of exercise psychology, an increasing number of scholars have begun to focus on the influence of exercise on mental health. However, a limited number of scholars have investigated the effects of exercise on mental health and related mechanisms among scientific and technological professionals. Thus, this study aimed to investigate the relationship between exercise and the mental health of scientific and technological professionals and the mediating roles of stress, resilience, and social support. Methods The respondents in this study were recruited using snowball sampling techniques and finally collected a total of 1,248 valid responses. Questionnaires were distributed through “www.wjx.cn (An online questionnaire website in China, which provides similar functions with Amazon MTurk)” in Henan province from November to December 2021. Participants were asked to complete the Positive Mental Health Scale, the stress subscale of the Depression Anxiety and Stress Scale (21 items), the Connor–Davidson Resilience Scale, and the Perceived Social Support Scale. A total of 1,248 valid responses were obtained. Results The mean exercise time of males was longer than that of females (t = 3.65, p < 0.01). Exercise and mental health were significantly associated with differences in age (F = −8.57, F = −4.66, p < 0.01) and educational background (F = 12.86, F = 7.14, p < 0.01). There were significant correlations among exercise, mental health, stress, resilience, and social support (p < 0.01). The direct effects of exercise on mental health were significant (β = 0.271, t = 9.577, p < 0.001), and the mediating effects of stress, resilience, and social support were also significant (χ2/df = 4.72, CFI = 0.940, TLI = 0.935, SRMR = 0.048, RMSEA = 0.055). Conclusion This study explored the effects of exercise on mental health and related mechanisms among scientific and technological professionals, which is beneficial to providing effective suggestions for managing and preventing the mental health of scientific and technological professionals. Future research should include a wider range of participants and adopt a longitudinal follow-up design to more deeply investigate the relationship between exercise and the mental health of scientific and technological professionals.